Effectiveness of Hypnoanalgesia in Paediatric Dermatological Surgery - Peláez Pérez Juana María; Sánchez Casado Marcelino; Quintana Díaz Manuel; Benhaiem Jean Marc; Escribá Alepuz Francisco Javier (MDPI AG, 2021)
Background and objective. Stress in surgical settings has subtle psychological and physiological repercussions in children. The objective is to evaluate whether hypnosedation is effective in reducing the doses of sedation and analgesia required during the periprocedural period in children undergoing dermatological surgery, without negatively affecting pain and satisfaction. Patients and methods: A prospective, longitudinal, observational study where paediatric patients (aged 5-16 years) scheduled for dermatological surgery were analysed according to whether they received hypnosis or distraction during surgery (both common procedures at the centre). As outcome measurements we used sedation doses (propofol) during surgery and the need for analgesia; pain assessment post-surgery and at 24 h using a visual analogue scale (VAS) or revised face pain scale (FPS-r) (both 0-10) depending on age, as well as patient and guardian satisfaction (on a scale of 0-10). Results: Of the 68 patients eligible during the follow-up period, 65 were included. Of these, 33 were treated with hypnosis and 32 with distraction. Children who underwent hypnosis required less total propofol (45.5 ± 11.8 mg vs. 69.3 ± 16.8 mg; p < 0.001) and metamizole in the immediate postoperative period (34.4% vs. 65.6%; p = 0.018). After 24 h, they required less ibuprofen (9.1% vs. 28.1%; p = 0.048) and paracetamol (48.5% vs. 75.0%; p = 0.028). Mean pain according to VAS or FPS-r at 24 h was 3.1 with hypnosis vs. 4.3 with distraction (p < 0.001). Overall satisfaction was higher in the hypnosis group (8.7 ± 0.1 vs. 8.1 ± 0.2; p = 0.009). Conclusions: Hypnoanalgesia in children undergoing dermatological outpatient surgery could not only reduce sedation and analgesia requirements, but also improve child and guardian(s) satisfaction.